Islamic legal restudy of effects of incorrect execution, in cutting punishments - Hasan Pour Lotfollah; Mahdi Movahedi moheb; Khosrov Momeni; Ahmad Mortazi (مطالعات فقه و حقوق اسلامی, 2020)
In executing of legal punishment such as cutting of hand or leg, it is probable to cut the opposite organ, by mistake, intentionally or by beneficence. In this case, the punishment of cutting is left, in view of famous theory in jurisprudence, contrary to another one. Although the in both opinion the pay of blood money is necessary, in supposition of intention of mistake and retaliation in supposition of mistake. In view of this article, by analysis of foundations, the view of un famous jurists ( revocation of legal punishments) is seem to correct, in both supposition of mistake and intention, and conformable to traditions that says it should be remain one hand and leg to offender, to accomplish basic and daily  Affairs. But this theory is reviewable, in conviction of executioner to retaliation or to pay blood money, because of contrariety with traditions, rule of Beneficence it will be in the interest of offender. (revocation of punishment, on one hand, and the right of demand of retaliation or receipt of blood money, on the other hand.) In opinion of authors, the equable way is that we say to revocation in both of intention and mistake, and at the same time we accept some proportional deterrent punishment (Taazir), in case of intention.